Negative plate, preparation method thereof and lithium ion battery

By using a MXene layer with a thickness of 10 to 20 nm and a graphite layer with a thickness of 120 to 130 μm in the negative electrode sheet of the lithium-ion battery, combined with the cold pressing method, the problem of poor lithium-ion battery lithium-ion battery performance and cycle stability during high-rate charging and discharging is solved, and the battery's mechanical performance and manufacturing yield are improved.

CN119742318AActive Publication Date: 2025-04-01EVE POWER CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411930482.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to lithium extraction and poor circulation stability during high-rate charging and discharging.

Method used

A negative electrode sheet is provided, which includes a current collector, a graphite layer and a MXene layer stacked in sequence. The thickness of the MXene layer is 10-20 nm, the thickness of the graphite layer is 120-130 μm, and the thickness ratio of the MXene layer and the graphite layer is 1:6500-12000. The negative electrode sheet is prepared by cold pressing method, with the first cold pressing speed ranging from 80 to 120 m/min and the second cold pressing speed ranging from 30 to 50 m/min.

Benefits of technology

The MXene layer forms a fast migration channel of ions on the surface of the graphite layer, promoting the rapid embedding and disengagement of lithium ions under high-rate charging and discharging conditions, reducing the risk of lithium extraction, and improving the charging and discharging efficiency and cycling stability of the battery. The mechanical properties of the MXene layer improve the tensile resistance of the negative electrode sheet, reduce crack problems during battery assembly, and improve manufacturing yield and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742318A_ABST
    Figure CN119742318A_ABST
Patent Text Reader

Abstract

The invention provides a negative plate, a preparation method thereof and a lithium ion battery. The negative plate comprises a current collector, a graphite layer and an MXene layer which are stacked in sequence, the thickness of the MXene layer ranges from 10 nm to 20 nm. The existence of the MXene layer in the negative electrode plate is beneficial to formation of a rapid ion migration channel on the surface of the graphite layer, rapid intercalation and deintercalation of lithium ions under a high-rate charging and discharging condition are promoted, and the risk of lithium precipitation in the high-rate charging and discharging process of the lithium ion battery is reduced; therefore, the charging and discharging efficiency and the cycling stability of the battery can be improved. According to the present invention, the MXene layer has good mechanical property, such that the tensile property of the negative electrode plate can be easily improved, and the wrinkling and cracking problems of the negative electrode plate during the battery assembly process can be reduced so as to easily improve the manufacturing yield and the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Graphite negative electrodes are widely used in lithium-ion batteries due to their excellent lithium insertion performance. However, their low theoretical specific capacity (372mAh / g) limits the development of high-capacity lithium-ion batteries. Researchers have improved the theoretical specific capacity of lithium-ion battery negative electrodes through methods such as graphite negative electrode surface modification and composite materials. For example, carbon coating technology and graphite / silicon composite negative electrode materials. However, these methods still cannot provide an ideal theoretical specific capacity for lithium-ion battery negative electrodes, and most of them require new process technologies, complex preparation processes, poor mechanical properties of the prepared materials, and high preparation costs. In addition, the battery is prone to lithium deposition and poor cycle stability during high-rate charge and discharge. In order to meet the ever-changing market demands, it is necessary to improve the performance of lithium-ion batteries from the perspectives of energy density, stability, and safety. Summary of the invention

[0003] The main purpose of the present application is to provide a negative electrode sheet and a preparation method thereof and a lithium ion battery, so as to solve the problem in the prior art that lithium ion batteries are prone to lithium deposition and poor cycle stability during high rate charge and discharge.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a negative electrode sheet is provided, which includes a current collector, a graphite layer and a MXene layer stacked in sequence; the thickness of the MXene layer is 10 to 20 nm.

[0005] Furthermore, the thickness of the graphite layer is 120-130 μm.

[0006] Furthermore, the thickness ratio of the MXene layer to the graphite layer is 1:6500-12000; and / or the compaction density of the negative electrode sheet is 1.48-1.75 g / cm 3 .

[0007] Furthermore, the material of the MXene layer is a single-layer MXene; further, the material of the MXene layer is Ti3C2T x ; and / or, the material of the graphite layer is graphite, a conductive agent and a binder; further, the mass ratio of graphite, the conductive agent and the binder is 8:1:1; further, the median particle size D50 of the graphite is 15 to 20 μm; and / or, the conductivity of the graphite is 10 2 ~10 3 S / m; and / or, the conductivity of a single layer of MXene is 10 4 S / m.

[0008] According to another aspect of the present application, a method for preparing the aforementioned negative electrode sheet is provided, and the preparation method includes: step S1, coating a graphite slurry on the surface of a current collector, and then performing a first cold pressing to obtain a graphite-covered current collector; step S2, coating a MXene slurry on the surface of a graphite layer of the graphite-covered current collector, and then performing a second cold pressing to obtain a negative electrode sheet.

[0009] Further, the speed of the first cold pressing is 80-120 m / min; and / or, the pressure of the first cold pressing is 15-70 MPa; and / or, the speed of the second cold pressing is 30-50 m / min; and / or, the pressure of the second cold pressing is 0.3-2 MPa; and / or, the compaction density of the graphite-covered current collector is 1.50-1.80 g / cm 3 .

[0010] Furthermore, the solid content of the above-mentioned graphite slurry is 67-69%; and / or the viscosity of the graphite slurry is 8000-25000 mPa·s; and / or the solid content of the MXene slurry is 9.8-10.2%; and / or the viscosity of the MXene slurry is 1000-2000 mPa·s.

[0011] Furthermore, the above-mentioned MXene slurry is prepared by mixing raw materials including a MXene material and a first solvent; further, the first solvent is selected from any one or more of anhydrous ethanol, N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide; and / or, the MXene material is a single-layer MXene material.

[0012] Furthermore, the above-mentioned graphite slurry is prepared by mixing raw materials including graphite, a conductive agent, a binder and a second solvent; further, the conductive agent is conductive carbon black; and / or the binder is polyvinylidene fluoride and / or sodium carboxymethyl cellulose; and / or the second solvent is selected from any one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0013] According to another aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0014] By applying the technical solution of the present application, the presence of the MXene layer in the negative electrode sheet of the present application helps to form a fast migration channel of ions on the surface of the graphite layer, promotes the rapid insertion and extraction of lithium ions under high-rate charge and discharge conditions, and helps to reduce the risk of lithium precipitation in the high-rate charge and discharge process of lithium-ion batteries, thereby helping to improve the charge and discharge efficiency and cycle stability of the battery. The MXene layer has good mechanical properties. The presence of the MXene layer helps to improve the tensile strength of the negative electrode sheet and reduce the problem of wrinkles and cracks in the negative electrode sheet during the battery assembly process, thereby helping to improve the manufacturing yield and service life of the battery. Compared with the prior art of using MXene to modify graphite to prepare the negative electrode sheet, the present application arranges the graphite layer between the current collector and the MXene layer, which helps to make the negative electrode sheet have better tensile strength and improve the insertion and extraction efficiency of lithium ions under high-rate charge and discharge conditions. In addition, there is a strong van der Waals force between the MXene layer and the graphite layer, which helps to reduce the use of binders and reduce the production cost of the negative electrode sheet. Controlling the thickness of the MXene layer within the above range helps to provide a smoother lithium ion deposition surface, reducing the local current density, thereby helping to reduce the formation of lithium dendrites, and further helping to enhance the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0016] Figure 1 The SEM image of the negative electrode sheet in Example 1 of the present application is shown.

[0017] The above drawings include the following reference numerals:

[0018] 1. MXene layer; 2. Graphite layer. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0020] Terminology explanation: MXene is a new type of two-dimensional material composed of transition metal carbides, nitrides or carbonitrides.

[0021] As analyzed in the background technology of this application, lithium-ion batteries in the prior art are prone to lithium deposition and poor cycle stability during high-rate charge and discharge. In order to solve the above problems, this application provides a negative electrode sheet and a preparation method thereof and a lithium-ion battery.

[0022] In a typical embodiment of the present application, a negative electrode sheet is provided, which includes a current collector, a graphite layer and a MXene layer stacked in sequence; the thickness of the MXene layer is 10 to 20 nm.

[0023] The presence of the MXene layer in the negative electrode sheet of the present application helps to form a fast migration channel of ions on the surface of the graphite layer, promotes the rapid embedding and extraction of lithium ions under high rate charge and discharge conditions, and helps to reduce the risk of lithium precipitation in the high rate charge and discharge process of lithium ion batteries, thereby helping to improve the charge and discharge efficiency and cycle stability of the battery. The MXene layer has good mechanical properties. The presence of the MXene layer helps to improve the tensile strength of the negative electrode sheet and reduce the problem of wrinkles and cracks in the negative electrode sheet during battery assembly, thereby helping to improve the manufacturing yield and service life of the battery. Compared with the prior art of using MXene to modify graphite to prepare the negative electrode sheet, the present application arranges the graphite layer between the current collector and the MXene layer, which helps to make the negative electrode sheet have better tensile strength and improve the embedding and extraction efficiency of lithium ions under high rate charge and discharge conditions. In addition, there is a strong van der Waals force between the MXene layer and the graphite layer, which helps to reduce the use of binders and reduce the production cost of the negative electrode sheet. Controlling the thickness of the MXene layer within the above range helps to provide a smoother lithium ion deposition surface, reducing the local current density, thereby helping to reduce the formation of lithium dendrites, and further helping to enhance the safety of the battery.

[0024] In one embodiment of the present application, the thickness of the graphite layer is 120-130 μm.

[0025] A graphite layer that is too thick will easily lead to a longer diffusion path for lithium ions within the layer, which is not conducive to improving the charging and discharging efficiency; a graphite layer that is too thin may easily break during battery manufacturing, winding, etc. Controlling the thickness of the graphite layer within the above range will help to increase the theoretical specific capacity and energy density of the battery while reducing the risk of structural damage due to volume expansion during the charging and discharging process.

[0026] In one embodiment of the present application, the thickness ratio of the MXene layer to the graphite layer is 1:6500-12000; and / or the compaction density of the negative electrode sheet is 1.48-1.75 g / cm 3 .

[0027] As a fast ion migration channel, if the thickness of the MXene layer is too thin relative to the graphite layer, it may not be able to effectively improve the migration speed of lithium ions; if it is too thick, it may occupy too much space, reduce the lithium ion storage sites of the graphite layer, and reduce the specific capacity of the battery. Controlling the thickness ratio of the MXene layer and the graphite layer within the above range helps to improve the energy density and cycle stability of lithium-ion batteries. Controlling the compaction density of the negative electrode sheet within the above range helps to achieve a higher energy density while having good electrochemical properties, reduce the volume change of the electrode material during the charge and discharge process, and reduce the probability of crack generation, thereby helping to improve the cycle stability of lithium-ion batteries. Appropriate compaction density helps to reduce the voids inside the electrode, reduce the risk of internal short circuits in the battery, and help to inhibit the formation of lithium dendrites, thereby enhancing battery safety. It should be noted that the density of the graphite layer is greater than that of the MXene layer, so the compaction density of the negative electrode sheet is smaller than that of the graphite layer.

[0028] In one embodiment of the present application, the material of the MXene layer is a single-layer MXene; in one embodiment of the present application, the material of the MXene layer is Ti3C2T x ; and / or, the material of the graphite layer is graphite, a conductive agent and a binder; in one embodiment of the present application, the mass ratio of graphite, the conductive agent and the binder is 8:1:1; in one embodiment of the present application, the median particle size D50 of the graphite is 15 to 20 μm and / or, the conductivity of the graphite is 10 2 ~10 3 S / m; and / or, the conductivity of a single layer of MXene is 10 4 S / m.

[0029] Single-layer MXene has high electronic and ionic conductivity. As the surface layer of the electrode material, it can effectively promote the rapid migration of lithium ions in the negative electrode and improve the charge and discharge efficiency and cycle performance of the battery. The thickness of the single-layer MXene is extremely thin, which helps to reduce the internal resistance of the electrode and improve the power density of the battery. The appropriate addition of binder helps to enhance the mechanical strength of the graphite layer and reduce the risk of cracks or detachment of the negative electrode during battery manufacturing and use. The addition of conductive agent helps to improve the conductive network of the graphite layer and further improve the cycle stability and service life of the battery. Controlling the mass ratio of graphite, conductive agent and binder within the above range helps to improve the cycle stability of the battery while increasing the energy density of the battery. Controlling the median particle size D50 of graphite within the above range helps to optimize the diffusion path of lithium ions in the graphite material and improve the efficiency of lithium ion embedding and extraction during the charge and discharge process, thereby helping to improve the charge and discharge efficiency and cycle life of the battery.

[0030] In another typical embodiment of the present application, a method for preparing the aforementioned negative electrode sheet is provided, and the preparation method comprises: step S1, coating the graphite slurry on the surface of the current collector, and performing a first cold pressing to obtain a graphite-covered current collector; step S2, coating the surface of the graphite layer of the graphite-covered current collector with MXene slurry, and performing a second cold pressing to obtain a negative electrode sheet.

[0031] In step S1, the graphite slurry is coated on the surface of the current collector and then subjected to the first cold pressing, which helps to form a uniform lithium ion storage platform. In step S2, the MXene slurry is coated on the surface of the graphite-covered current collector and then subjected to the second cold pressing, which helps to make the MXene layer evenly distributed on the surface of the graphite layer, forming a rapid migration channel for lithium ions, and at the same time helps to improve the integrity and stability of the MXene layer. The MXene layer and the graphite layer are connected by van der Waals forces, which helps to reduce the use of binders and reduce the production cost of the negative electrode sheet. After two cold pressings, it helps to form a negative electrode sheet with a higher compaction density, thereby helping to reduce the impedance inside the electrode and improve the overall electrochemical activity of the lithium-ion battery. The preparation method of the present application is simple, does not require additional equipment costs, and has a low production cost.

[0032] In one embodiment of the present application, the speed of the first cold pressing is 80-120 m / min; and / or, the pressure of the first cold pressing is 15-70 MPa; and / or, the speed of the second cold pressing is 30-50 m / min; and / or, the pressure of the second cold pressing is 0.3-2 MPa; and / or, the compaction density of the graphite-covered current collector is 1.50-1.80 g / cm 3 .

[0033] If the speed of the first cold pressing is too fast, it may lead to uneven distribution of the graphite layer, while if it is too slow, it is not conducive to improving production efficiency. Controlling the speed of the first cold pressing within the above range helps to improve the uniformity of the distribution of the graphite layer. Controlling the pressure of the first cold pressing within the above range helps to increase the compaction density of the graphite layer and reduce the internal voids, thereby helping to improve the migration speed of lithium ions and the efficiency of the electrochemical reaction. Controlling the speed and pressure of the second cold pressing within the above range helps to optimize the combination of the MXene layer and the graphite layer, improve the density and stability of the MXene layer, thereby helping to further improve the rapid migration of lithium ions between electrode materials and enhance the mechanical strength of the electrode. Controlling the compaction density of the graphite-covered current collector within the above range helps to increase the graphite loading per unit volume and improve the energy density of the battery; at the same time, it helps to reduce the porosity inside the electrode and reduce the impedance, thereby helping to improve the charge and discharge efficiency and cycle stability of the battery.

[0034] In order to improve the distribution and dispersion uniformity of the graphite layer and the MXene layer, in one embodiment of the present application, the solid content of the above-mentioned graphite slurry is 67-69%; and / or, the viscosity of the graphite slurry is 8000-25000 mPa·s; and / or, the solid content of the MXene slurry is 9.8-10.2%; and / or, the viscosity of the MXene slurry is 1000-2000 mPa·s.

[0035] In one embodiment of the present application, the above-mentioned MXene slurry is prepared by mixing raw materials including a MXene material and a first solvent; in one embodiment of the present application, the first solvent is selected from any one or more of anhydrous ethanol, N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide; and / or, the MXene material is a single-layer MXene material.

[0036] Controlling the type of the first solvent within the above range helps to improve the uniformity and stability of the MXene slurry.

[0037] In one embodiment of the present application, the preparation method of the above-mentioned single-layer MXene material includes: dissolving the accordion-shaped multilayer MXene in water and then centrifuging it, setting the centrifuge speed to 5000r / min, removing the upper clear liquid after the centrifugation, re-adding water to the centrifuge tube, and repeating the above steps until no obvious solid-liquid stratification phenomenon can be observed after the centrifugation, at which time the solution contains a single-layer MXene material.

[0038] In one embodiment of the present application, the above-mentioned graphite slurry is prepared by mixing raw materials including graphite, a conductive agent, a binder and a second solvent; in one embodiment of the present application, the conductive agent is conductive carbon black; and / or the binder is polyvinylidene fluoride and / or sodium carboxymethyl cellulose; and / or the second solvent is selected from any one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0039] Controlling the types of the conductive agent, the binder, and the second solvent within the above range helps to improve the interaction between the components, thereby helping to improve the uniformity and stability of the graphite slurry.

[0040] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0041] Since the above-mentioned lithium-ion battery contains the negative electrode sheet of the present application, the probability of lithium deposition occurring in the lithium-ion battery during high-rate charge and discharge is relatively low.

[0042] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0043] Example 1

[0044] The accordion-shaped multilayer MXene was dissolved in water and centrifuged. The MXene was Ti3C2T x , set the centrifuge speed to 5000r / min, remove the supernatant after centrifugation, add water to the centrifuge tube again, and repeat the above steps until no obvious solid-liquid stratification phenomenon can be observed after centrifugation. At this time, the solution contains a single layer of MXene, and the conductivity of the single layer of MXene is 10 4 The monolayer MXene was dispersed in N-methyl-2-pyrrolidone to obtain a MXene slurry, in which the solid content of the MXene slurry was 10% and the viscosity was 1500 mPa·s.

[0045] Graphite, conductive carbon black and polyvinylidene fluoride were dispersed in N-methyl-2-pyrrolidone in a mass ratio of 8:1:1 to obtain a graphite slurry. The median particle size D50 of the graphite was 15 μm and the conductivity was 10 2 S / m, the solid content of the graphite slurry is 68.8%, and the viscosity is 18200mPa·s.

[0046] The graphite slurry was coated on the surface of a copper foil with a thickness of 5 μm, and then dried and cold pressed for the first time at a speed of 100 m / min and a pressure of 20 MPa. The thickness of the graphite layer was controlled to be 125 μm, and a graphite-covered copper foil was obtained with a compaction density of 1.65 g / cm 3 The above MXene slurry was coated on the surface of the graphite layer, and after drying, a second cold pressing was performed at a speed of 40m / min and a pressure of 1MPa. The thickness of the MXene layer was controlled to be 15nm to obtain a negative electrode sheet. The compaction density of the negative electrode sheet was 1.62g / cm 3 , the thickness ratio of MXene layer to graphite layer is 1:8300.

[0047] Example 2

[0048] The difference from Example 1 is that the thickness of the MXene layer is controlled to be 20 nm, the thickness of the graphite layer is controlled to be 130 μm, and finally a negative electrode sheet is obtained. The thickness ratio of the MXene layer to the graphite layer is 1:6500.

[0049] Example 3

[0050] The difference from Example 1 is that the thickness of the MXene layer is controlled to be 10 nm, the thickness of the graphite layer is controlled to be 120 μm, and finally a negative electrode sheet is obtained. The thickness ratio of the MXene layer to the graphite layer is 1:12000.

[0051] Example 4

[0052] The difference from Example 1 is that the thickness of the MXene layer is controlled to be 10 nm, the thickness of the graphite layer is controlled to be 130 μm, and finally a negative electrode sheet is obtained. The thickness ratio of the MXene layer to the graphite layer is 1:13000.

[0053] Example 5

[0054] The difference from Example 1 is that the median particle size D50 of graphite is 20 μm, and a negative electrode sheet is finally obtained.

[0055] Example 6

[0056] The difference from Example 1 is that the median particle size D50 of graphite is 25 μm, and a negative electrode sheet is finally obtained.

[0057] Example 7

[0058] The difference from Example 1 is that the speed of the first cold pressing is 80 m / min, the pressure of the first cold pressing is 15 MPa, and the compaction density of the graphite-covered copper foil is 1.50 g / cm 3 Finally, the negative electrode sheet is obtained. The compaction density of the negative electrode sheet is 1.48g / cm 3 .

[0059] Example 8

[0060] The difference from Example 1 is that the speed of the first cold pressing is 120 m / min, the pressure of the first cold pressing is 70 MPa, and the compaction density of the graphite-covered copper foil is 1.72 g / cm 3 Finally, the negative electrode sheet is obtained. The compaction density of the negative electrode sheet is 1.70g / cm 3 .

[0061] Example 9

[0062] The difference from Example 1 is that the speed of the first cold pressing is 70 m / min, the pressure of the first cold pressing is 80 MPa, and the compaction density of the graphite-covered copper foil is 1.80 g / cm 3 Finally, the negative electrode sheet is obtained. The compaction density of the negative electrode sheet is 1.75g / cm 3 .

[0063] Example 10

[0064] The difference from Example 1 is that the speed of the second cold pressing is 30 m / min, the pressure of the second cold pressing is 0.3 MPa, and the negative electrode sheet is finally obtained. The compaction density of the negative electrode sheet is 1.68 g / cm 3 .

[0065] Embodiment 11

[0066] The difference from Example 1 is that the speed of the second cold pressing is 50 m / min, the pressure of the second cold pressing is 2 MPa, and the negative electrode sheet is finally obtained. The compaction density of the negative electrode sheet is 1.63 g / cm 3 .

[0067] Example 12

[0068] The difference from Example 1 is that the speed of the second cold pressing is 20 m / min, the pressure of the second cold pressing is 3 MPa, and the negative electrode sheet is finally obtained. The compaction density of the negative electrode sheet is 1.64 g / cm 3 .

[0069] Example 13

[0070] The difference from Example 1 is that the solid content of the MXene slurry is 9.8%, the viscosity of the MXene slurry is 1000 mPa·s, and finally a negative electrode sheet is obtained.

[0071] Embodiment 14

[0072] The difference from Example 1 is that the solid content of the MXene slurry is 10.2%, the viscosity of the MXene slurry is 2000 mPa·s, and finally a negative electrode sheet is obtained.

[0073] Embodiment 15

[0074] The difference from Example 1 is that the solid content of the MXene slurry is 15%, the viscosity of the MXene slurry is 3000 mPa·s, and finally a negative electrode sheet is obtained.

[0075] Comparative Example 1

[0076] The difference from Example 1 is that the coating of MXene slurry is cancelled, and finally a negative electrode sheet is obtained.

[0077] Comparative Example 2

[0078] The difference from Example 1 is that the graphite slurry and the MXene slurry are mixed and coated on the surface of a copper foil with a thickness of 5 μm, and then cold pressed at a speed of 100 m / min and a pressure of 20 MPa after drying to finally obtain a negative electrode sheet.

[0079] Battery preparation

[0080] Positive electrode sheet: Lithium iron phosphate positive electrode material, conductive carbon black and polyvinylidene fluoride were mixed in an N-methylpyrrolidone (NMP) solvent in a weight ratio of 90:5:5 to prepare a positive electrode mixture, and the mixture was applied on an aluminum foil, and the resultant was dried and then roll-pressed to prepare a positive electrode sheet.

[0081] Electrolyte: An electrolyte was prepared by dissolving 1.15 M lithium hexafluorophosphate in an organic solvent formed of ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (mixing volume ratio of EC / DMC / EMC=3 / 4 / 3).

[0082] The negative electrode sheet, porous polyethylene separator and positive electrode sheet prepared in the embodiment and comparative example are used to prepare an electrode assembly, the electrode assembly is placed in a shell, and then an electrolyte is injected into the shell to prepare a battery.

[0083] Performance Testing

[0084] The battery prepared above was discharged at a constant current (CC) at a rate of 1C to 20% SOC at 25°C, and then charged at a constant current (CC) at a rate of 1C to 80% SOC, and the charging time from 20% to 80% SOC at a rate of 1C was recorded.

[0085] The battery prepared above was discharged at a constant current (CC) at a rate of 5C to 20% SOC at 25°C, and then charged at a constant current (CC) at a rate of 5C to 80% SOC, and the charging time from 20% to 80% SOC at a rate of 5C was recorded.

[0086] The battery prepared above was charged to 3.65V at 1C under constant current (CC) conditions at 25°C, and then discharged to 2.5V at 1C rate under constant current (CC) conditions. This was considered a cycle, and the test was repeated 4000 times. The capacity retention rate at the 4000th cycle was measured.

[0087] The results of the battery's 20%-80% SOC charging time at 1C rate, 20%-80% SOC charging time at 5C rate, and capacity retention rate after 4000 cycles at 1C rate are shown in Table 1.

[0088] Table 1

[0089]

[0090]

[0091] From the data of the embodiments and comparative examples in Table 1, it can be seen that in comparative example 1, in the absence of MXene, the battery cannot be normally charged and discharged at a rate of 5C; in comparative example 2, the negative electrode active layer formed by mixing MXene with graphite is not conducive to improving the cycle stability at a high rate. The present application helps to promote the rapid insertion and extraction of lithium ions under high rate charge and discharge conditions by covering a layer of MXene on the surface of the graphite layer, thereby helping to reduce the risk of lithium precipitation and making the battery have higher cycle stability at a high rate.

[0092] Figure 1 This is the SEM image of the negative electrode sheet in Example 1 of the present application, from Figure 1 It can be seen that MXene layer 1 tightly covers the surface of graphite layer 2.

[0093] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:

[0094] The presence of the MXene layer in the negative electrode sheet of the present application helps to form a fast migration channel of ions on the surface of the graphite layer, promotes the rapid embedding and extraction of lithium ions under high rate charge and discharge conditions, and helps to reduce the risk of lithium precipitation in the high rate charge and discharge process of lithium ion batteries, thereby helping to improve the charge and discharge efficiency and cycle stability of the battery. The MXene layer has good mechanical properties. The presence of the MXene layer helps to improve the tensile strength of the negative electrode sheet and reduce the problem of wrinkles and cracks in the negative electrode sheet during battery assembly, thereby helping to improve the manufacturing yield and service life of the battery. Compared with the prior art of using MXene to modify graphite to prepare the negative electrode sheet, the present application arranges the graphite layer between the current collector and the MXene layer, which helps to make the negative electrode sheet have better tensile strength and improve the embedding and extraction efficiency of lithium ions under high rate charge and discharge conditions. In addition, there is a strong van der Waals force between the MXene layer and the graphite layer, which helps to reduce the use of binders and reduce the production cost of the negative electrode sheet. Controlling the thickness of the MXene layer within the above range helps to provide a smoother lithium ion deposition surface, reducing the local current density, thereby helping to reduce the formation of lithium dendrites, and further helping to enhance the safety of the battery.

[0095] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector, a graphite layer and a MXene layer stacked in sequence; the thickness of the MXene layer is 10 to 20 nm.

2. The negative electrode sheet according to claim 1, characterized in that: The thickness of the graphite layer is 120-130 μm.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The thickness ratio of the MXene layer to the graphite layer is 1:6500-12000; and / or the compaction density of the negative electrode sheet is 1.48-1.75 g / cm 3 .

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The material of the MXene layer is a single-layer MXene; preferably, the material of the MXene layer is Ti3C2T x ; And / or, the material of the graphite layer is graphite, a conductive agent and a binder; Preferably, the mass ratio of the graphite, the conductive agent and the binder is 8:1:1; Further preferably, the median particle size D50 of the graphite is 15 to 20 μm; And / or, the electrical conductivity of the graphite is 10 2 ~10 3 S / m; and / or, the electrical conductivity of the monolayer MXene is 10 4 S / m.

5. A method for preparing a negative electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Step S1, coating the surface of the current collector with graphite slurry and then performing a first cold pressing to obtain a current collector covered with graphite; Step S2, after coating the MXene slurry on the surface of the graphite layer of the graphite-covered current collector, performing a second cold pressing to obtain the negative electrode sheet.

6. The preparation method according to claim 5, characterized in that: The speed of the first cold pressing is 80-120 m / min; and / or, the pressure of the first cold pressing is 15-70 MPa; and / or, the speed of the second cold pressing is 30-50 m / min; and / or, the pressure of the second cold pressing is 0.3-2 MPa; and / or, the compaction density of the graphite-covered current collector is 1.50-1.80 g / cm 3 .

7. The preparation method according to any one of claims 5 or 6, characterized in that The solid content of the graphite slurry is 67-69%; and / or the viscosity of the graphite slurry is 8000-25000 mPa·s; and / or the solid content of the MXene slurry is 9.8-10.2%; and / or the viscosity of the MXene slurry is 1000-2000 mPa·s.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The MXene slurry is prepared by mixing raw materials including a MXene material and a first solvent; Preferably, the first solvent is selected from any one or more of anhydrous ethanol, N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide; And / or, the MXene material is a single-layer MXene material.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The graphite slurry is prepared by mixing raw materials including graphite, a conductive agent, a binder and a second solvent; Preferably, the conductive agent is conductive carbon black; And / or, the binder is polyvinylidene fluoride and / or sodium carboxymethyl cellulose; And / or, the second solvent is selected from any one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Negative plate, preparation method thereof and lithium ion battery

    CN113421992A

  • Inert lithium powder composite slurry and preparation method thereof, lithium-supplementing negative plate and preparation method thereof, and lithium ion battery

    CN115513454A

  • Negative pole piece and preparation method thereof, battery and vehicle

    CN116565109A

  • Interface protection layer material and preparation method and application thereof

    CN118270757A

  • Application of MXene in inhibiting low-temperature lithium dendrite precipitation of negative electrode of lithium ion battery, negative electrode, lithium ion battery and vehicle

    CN118748253A